Hyperbaric Vacuum‐Based Artificial Muscles for High‐Performance Actuation. (24th July 2022) - Coutinho, Altair; Park, Jae Hyeong; Jamil, Babar; Choi, Hyouk Ryeol; Rodrigue, Hugo
Abstract : Existing pneumatic artificial muscles generally rely on the use of either positive or negative pressure for actuation with each having their own advantages and disadvantages. Herein, a hyperbaric vacuum‐based artificial muscle (Hyper‐VAM) making use of both positive and negative pressures almost interchangeably is described. This is done by placing a vacuum‐based actuator inside a hyperbaric chamber which enables both the large deformations possible using negative pressure, and large forces through the action of high pressure differential, exceeding those possible using only negative pressure. This actuator can lift heavy payloads (up to 80 kg) for its entire contraction range, with large deformations (89.1% contraction of the active length) and high power (maximum power of 101.3 W), while using relatively low pressures, which can be supplied by a portable pneumatic pump. By exchanging air between the two chambers in closed‐loop pneumatic actuation, this actuator can also be driven using a single pump without exchanging air with the environment and its position can be controlled using a single pneumatic regulator. Abstract : Herein, a hyperbaric vacuum‐based artificial muscle (Hyper‐VAM) making use of both positive and negative pressures almost interchangeably is described. This actuator can lift heavy payloads for its entire contraction range (up to 80 kg), with large deformations (89.1% contraction ratio), and high power (101.3 W), while using relatively low pressures which can be supplied by a portable pneumatic pump.